ANALISIS PENGARUH CONSUMER ATTRIBUTES, BRAND AWARENESS ATTRIBUTES, DAN BRAND IMAGE ATTRIBUTES TERHADAP BRAND EQUITY DAN KEPUTUSAN MEMILIH JASA PENDIDIKAN (STUDI KASUS PADA PERGURUAN TINGGI DI BENGKALIS) - Dwi Astuti (Politeknik Negeri Bengkalis, 2017)
Abstract : The purposes of this study were to analyze the influence of consumerattributes, brand awareness attributes, and brand image attributes simultaneously and partially on the brand equity of higher education institution inBengkalis, the effect of brand equity on the decision of choosing a highereducation institution in Bengkalis, and the indirect influence of consumerattributes, brand awareness attributes, dan brand image attributes throughbrand equity toward decision of choosing a higher education institution inBengkalis. The population in this study were all 2,819 active students enrolledat three higher education institutions located in Bengkalis Islands. Thesamples were 100 students with the sampling technique used was Proportionate Stratified Random Sampling. The research data were analyzed usingpath analysis and processed using SPSS for Windows version 17. The result ofanalysis showed that the consumer attributes, brand awareness attributes, andbrand image attributes jointly affect the brand equity of higher education inBengkalis. Individually, There is also an influence of consumer attributes,brand awareness attributes, dan brand image attributes toward brand equity ofhigher education institution in Bengkalis. In addition, the results obtained alsoshowed that there was an influence of brand equity on the decision of choosinga higher education institution in Bengkalis, in which, the higher and the morethe quality of brand equity have will directly increase the consumer's decisionto choose a higher education institution and vice versa. Beside that, The resultof analysis also showed that the better and higher the quality of brand equity,the better the influence of consumer attributes, brand awareness attributes, danbrand image attributes toward the decision of choosing a higher educationinstitution in Bengkalis.Keywords : Consumer Attributes, Brand Awareness Attributes, Brand ImageAttributes, Brand Equity, Decision Choice.